Algaculture integration in conventional wastewater treatment plants: Anaerobic digestion comparison of primary and secondary sludge with microalgae biomass. (May 2015) - Mahdy, Ahmed; Mendez, Lara; Ballesteros, Mercedes; González-Fernández, Cristina
Highlights: Microalgae anaerobic biodegradability was higher than that of secondary sludge. Thermal pretreatment was more effective on microalgae than on secondary sludge. Pretreated microalgae and primary sludge codigestion enhanced methane yields by 15%. Algae and municipal wastewater sludge can be cosubstrates for biogas production. Abstract: This study evaluated the feasibility of using microalgae biomass as feedstock for anaerobic digestion together with other biomasses (primary and secondary sludge) normally generated in WWTP. Raw microalgae biomass anaerobic biodegradability (33%) was higher than that of secondary sludge (23%). Thermal pretreatment enhanced 62% and 16% methane yield for Chlorella vulgaris and secondary sludge, respectively. When both substrates were codigested, methane yields remained low. On the other hand, primary sludge supported the highest anaerobic biodegradability (97%) and when combined with thermally pretreated C. vulgaris, methane yields were higher (13–17%) than the ones expected theoretically. Despite the high protein content of those substrates and the high nitrogen mineralization, no ammonia inhibition was detected. Thereby, this study showed that algae biomass is a potential cosubstrate for biogas production together with municipal wastewater sludge.